1998
DOI: 10.1002/(sici)1097-4598(199810)21:10<1334::aid-mus16>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Transient weakness and compound muscle action potential decrement in myotonia congenita

Abstract: Twenty-five Turkish patients with recessive myotonia congenita (RMC), 16 of whom had genetic confirmation, were studied. Nineteen had transient weakness. In the upper extremities, onset age of transient weakness was usually in the early teens. All untreated RMC patients had a compound muscle action potential decrement of ജ25%, usually above 50%, with repetitive nerve stimulation at 10/s for 5 s. Patients with other nondystrophic diseases with myotonia, except 1 patient with dominant myotonia congenita, had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 11 publications
4
21
0
1
Order By: Relevance
“…The fact that functional ClC-1 channels were observed for all of these mutants indicates a specific effect on ATP modulation rather than nonspecific disruption of the CBS domain structure, as such disruption also appears to disrupt channel function (21). We also tested the effect of a myotonia-associated mutation, G859D (12,23), in CBS 2, but functional ClC-1 channels were not observed, presumably because of the disruption of the CBS domain structure. Interestingly, all of the mutations that reduced the effect of ATP also shifted the voltage dependence of common gating in the absence of nucleotide to be more like that of wild type ClC-1 in the presence of ATP (Fig.…”
Section: Atp Modulation Is Mediated By Cbs Domains Of Clc-1-havingmentioning
confidence: 92%
See 1 more Smart Citation
“…The fact that functional ClC-1 channels were observed for all of these mutants indicates a specific effect on ATP modulation rather than nonspecific disruption of the CBS domain structure, as such disruption also appears to disrupt channel function (21). We also tested the effect of a myotonia-associated mutation, G859D (12,23), in CBS 2, but functional ClC-1 channels were not observed, presumably because of the disruption of the CBS domain structure. Interestingly, all of the mutations that reduced the effect of ATP also shifted the voltage dependence of common gating in the absence of nucleotide to be more like that of wild type ClC-1 in the presence of ATP (Fig.…”
Section: Atp Modulation Is Mediated By Cbs Domains Of Clc-1-havingmentioning
confidence: 92%
“…Although the functional role of CBS domains in ClC proteins remains unclear, their importance to channel function is underlined by disease causing mutations. In humans mutations in the CBS domains of ClC-1 underlie congenital myotonia (23), in ClC-2, generalized idiopathic epilepsy (24), in ClC-5, hypercalciuric nephrolithiasis (25), in ClC-Kb, Bartter syndrome, (26) and in ClC-7, infantile malignant osteopetrosis (27).…”
mentioning
confidence: 99%
“…Previous studies indicated that Y261C and G859D mutation behaved as recessive alleles, located in the G helix and the CBS2 domain of CLC-1 respectively. [11][12][13] It is most interesting to note that the 2 mutations were found in her unaffected father but not mother, suggesting that these 2 mutations are located on the same chromosome. This lack of symptomatology may be attributable to incomplete penetrance, which was described in other families with dominant myotonia congenita.…”
Section: Discussionmentioning
confidence: 99%
“…Various stimulation paradigms have been proposed. Probably the most widely used is a frequency of 10 Hz for 5 s. Regarding the sensitivity and specificity using this method, Deymeer et al 26 evaluated a cohort of 25 patients with rMC, 6 with dMC, 1 with paramyotonia congenita, and 1 with HyperPP. Their sensitivity was 96% for rMC using a decrement cutoff of Ն25%, with 88% specificity in differentiating rMC from other forms of nondystrophic myotonia (dMC, HyperPP, or paramyotonia congenita).…”
Section: Repetitive Nerve Stimulation Studies and Transient Paresismentioning
confidence: 99%
“…In contrast, a 1:1 expression of I290M and P480L causes severe gating abnormalities, corresponding to the full penetrance and often pronounced myotonia of heterozygous patients. (b) Dominant mutations cause different degrees of CMAP decrement at 10-Hz repetitive nerve stimulation (ColdingJørgensen et al, 20 Deymeer et al 26 ). No decrement is observed in patients heterozygous for the 'mild' G200R mutation, whereas a pronounced decrement is seen in patients heterozygous for the P480L mutation.…”
Section: Quantification Of Myotoniamentioning
confidence: 99%